Pelatihan Digital Marketing untuk Ibu-Ibu Rumah Tangga di Kecamatan Gempol, Kabupaten Pasuruan, Provinsi Jawa Timur - Iman Santoso, Berkah; Mulyasari Agustini, Prima; Kurnia, Ari (Indonesian Journal for Social Responsibility, 2020)
Household economics reinforcement, especially in village areas, has become responsibility among government through village community empowerment programs and the family economic activity. Housewives, who were managing household economy, often lack of time, power and resources while managing their household economy. Meanwhile, the husband has main responsibility to support household economy to do their job in earning money. He also has limitation to fulfil household needs. One of the alternative breakthrough to empower housewives is using the digital media as an appropriate media which is one of the goods and services home production marketing channel through digital marketing. The writers has given digital marketing workshop using social media which has been installed in audience’s smartphone, in location Kejapanan Village, Gempol, Pasuruan, Jawa Timur to its related purpose. Furthermore, the workshop is aimed to develop creative-entrepreneur housewives in Kejapanan Villages which are able to use digital marketing media for promoting household products and services independently.